CALCULATION POLYCARBONATE PANELS CONSIDERING CHANGES IN STRENGTH PROPERTIES OF INDICATORS TENSILE STRENGTH AND MODULUS OF ELASTICITY - and (Municipal economy of cities. Series: «Economy science», 2013)
<span style="background-color: #ffffff;" title="Рассматриваются вопросы методического подхода к расчету поликарбонатных двухслойных панелей, которые наиболее часто используются в ограждающих конструкциях покрытий зданий и сооружений, с учетом изменения прочностных свойств в процессе эксплуатации.">The problems of a methodological approach to the calculation of two-layer polycarbonate panels, which are most commonly used in building envelopes covering buildings and structures, taking into account the changes in mechanical properties during operation...